Enhancing potential field data using its dip angle. Issue 3 (17th May 2022) - Cooper, G.R.J.
ABSTRACT: The dip angle of a seismic horizon is a commonly used attribute of seismic data. It has the useful property that it is almost independent of the amplitude of the features being analysed. When appropriately rescaled, it can also be a useful edge detector for potential field data. Rescaling is necessary because the gradients of potential field data are not dimensionless. The rescaling also allows the amplitude balancing effect to be controlled, which is useful when poor quality data are being processed. The dip angle of synthetic data and aeromagnetic data from South Africa are analysed and the filter is found to be effective.